Brahui Script a Research Review - Ali, Abid; Shahwani, Shabir Ahmed; Ali, Liaquat (sourcecoder, 2024)
This research article examines the various scripts used in the Brahui language, a linguistic system as ancient as its speakers. Over the centuries, Brahui has employed different writing systems, each reflective of broader historical and cultural shifts. The discussion begins by exploring early communicative methods, such as pictorial representations, which evolved into phonetic letters and contributed to the development of structured language systems. Brahui, like many other languages, initially utilized a pictorial script, before transitioning to other writing forms such as Kharoshti and Nastaliq. This study provides a comprehensive historical overview of these scripts, highlighting the significant role they have played in the evolution of Brahui written tradition